Live, Attenuated Venezuelan Equine Encephalitis Virus Vaccine (TC83) Causes Persistent Brain Infection in Mice with Non-functional αβ T-Cells - Taylor, Katherine; Kolokoltsova, Olga; Ronca, Shannon E.; Estes, Mark; Paessler, Slobodan (Frontiers in Microbiology, 2017)
Intranasal infection with vaccine strain of Venezuelan equine encephalitis virus (TC83) caused persistent viral infection in the brains of mice without functional αβ T-cells (αβ-TCR -/-). Remarkably, viral kinetics, host response gene transcripts and symptomatic disease are similar between αβ-TCR -/- and wild-type C57BL/6 (WT) mice during acute phase of infection (0-13 days post-infection (dpi)). While WT mice clear infectious virus in the brain by 13 dpi, αβ-TCR -/- maintain infectious virus in the brain to 92 dpi. Persistent brain infection in αβ-TCR -/- correlated with inflammatory infiltrates and elevated cytokine protein levels in the brain at later time points. Persistent brain infection of αβ-TCR -/- mice provides a novel model to study prolonged alphaviral infection as well as the effects and biomarkers of long-term viral inflammation in the brain.